Ceramic powder characterisation - Yip, Jerome Jie-Long (2014)
Selective Laser Melting (SLM) is an additive manufacturing process which utilizes powder to create highly intricate 3 dimensional (3D) objects with the aid of computer aided design (CAD) files. As the technology grows more popular, it is slowly widening its applications to various industries.